Analytics and iGaming - Michael L Naraine; Cheri Bradish (Journal of Applied Sports Management, 2022)
Analytics has become quite the buzzword, but its application to discover, interpret, and communicate meaningful patterns from voluminous, velocitous, and varied data still resonates in the sport industry, and has an incredibly important place in modern sports betting. Specifically, big data and analytics (BDA) can help address marketing issues as iGaming in North America enters its infancy and attempts to establish a mature marketplace. This article is dedicated to unpacking the iGaming model and uncovers where BDA could and should be applied to derive greater insights on sports betting consumer behavior.
Keywords: sport analytics; igaming